Kompetensi Guru dalam Perspektif Imâm Abȗ Ḥanȋfah: Kajian Kitab Waṣiyyah Al-Imâm Abȋ Ḥanȋfah Li Yȗsuf Ibn Khâlid As-Samtiyy - Daulay, Rosul Pilihan; Arsyad, Junaidi; Budianti, Yusnaili (el Buhuth: Borneo Journal of Islamic Studies, 2024)
This research aims to analyze: Biography and socio-political setting of Imâm Abȗ Ḥanȋfah's scholarship, personality and social competence of teachers according to the views of Imâm Abȗ Ḥanȋfah in the book Waṣiyyah Al-Imâm Abȋ Ḥanȋfah li Yȗsuf ibn Khâlid As-Samtiyy and the relevance of Imâm Abȗ Ḥanȋfah's views on competence teacher's personality and social life in the context of today's Islamic education.The research method is qualitative with a library research approach. The data analysis technique uses content analysis, namely: studying and reviewing the book Waṣiyyah Al-Imâm Abȋ Ḥanȋfah li Yȗsuf ibn Khâlid As-Samtiyy, recording the material in the form of a short summary , look for other references and collect things related to research, match with relevant books, analyze reading sources in more depth and draw conclusions from the research results.The results of the research include: Imâm Abȗ Ḥanȋfah was a great scholar who founded Mażhab Ḥanâfî. He is also a cleric and trader in Kufa City, where he was born. Imâm Abȗ Ḥanȋfah refused to be appointed Qâḍi by the king because he felt unworthy of having more 'âlim clerics. This refusal meant that he was considered to have opposed the king and was imprisoned. Imâm Abȗ Ḥanȋfah considers it important for a teacher to have personality and social competence. This view is proven by the will given to his student, Yȗsuf bin Khâlid As-Samtiyy. These wills consist of 16 personal competence wills and 58 social competence wills. This will must be implemented by teachers in interacting in educational institutions and in society. Imâm Abȗ Ḥanȋfah's aim in giving this testament is so that his students and current teachers can be accepted in the educational environment accompanied by a feeling of love from the students.